Enrichment of Anaerobic Ammonium Oxidation (Anammox) bacteria for Biological Nitrogen removal of wastewater - Yusof Norjan, Abdullah Hanisom, Samsudin Syakirah, Hassan Mohd Ali, (N/A, 2012)
Enrichment of Anaerobic Ammonium Oxidation (Anammox) bacteria for Biological Nitrogen removal of wastewater by Yusof Norjan, Abdullah Hanisom, Samsudin Syakirah, Hassan Mohd Ali,